Exploring the potential anti-psoriatic properties of a semi-synthetic 14-Deoxy-11,12-didehydroandrographolide derivative. - Stanslas, Johnson; Sugumaran, Dineshwar; How, Kang Nien; Chee, Audrey Hui Yong (Universiti Putra Malaysia, 2024)
Introduction: Psoriasis is a chronic skin disease characterized by inflammation and hyperproliferation that affects around 2% to 3% of the global population. Currently, no control is available for psoriasis and existing treatments have limitations due to side effects, necessitating the development of safer and more effective anti-psoriatic agents. This study was carried out to determine the anti-psoriatic activity of the 14-deoxy-11,12-didehydroandrographolide (DDAG) derivative via the inhibition of inflammatory pathways, such as nuclear factor kappa light chain enhancer of activated B cells (NF-κB) and mitogen-activated protein kinase (MAPK). Methods: Spontaneously immortalized human keratinocyte (HaCaT) and immortalized mouse macrophage (RAW264.7) cells, respectively were treated with andrographolide (AGP), DDAG, SRS49 (semi-synthesized DDAG), and gemcitabine (positive control). The cytotoxicity was evaluated via MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay. Results: AGP (IC50: 3.03 µM) and gemcitabine (IC50: 0.075 µM) exhibited high cytotoxicity against HaCaT cells, while DDAG did not exhibit any toxicity even at high concentration (100 µM). AGP and gemcitabine also displayed high cytotoxicity against RAW264.7 cells, with DDAG showing moderate cytotoxicity. SRS49 exhibit higher cytotoxicity against HaCaT cells (IC50: 48.67 µM) compared to RAW264.7. SRS49 demonstrated anti-proliferative activity against HaCaT cells, indicating potential anti-psoriatic properties. Further studies will be conducted to investigate the effect of SRS49 against proteins involved in NF-κB and MAPK pathways through western blot analysis. Conclusion: SRS49 exhibited promising anti-psoriatic properties by selectively inhibiting HaCaT cell proliferation, making it a potential candidate for psoriasis treatment. However, additional studies are needed to determine whether SRS49 has anti-inflammatory activity in HaCaT cells induced with proinflammatory agents, such as tumour necrosis factor-alpha (TNF-a) and interleukin 17 (IL-17) to further support its efficacy against psoriasis.